Repertorio Americano: An early contribution to knowledge management - Montero Bustabad, Pedro (2018)
It discusses how the journal Repertorio Americano based on the characteristics of management defined by Thomas Davenport knowledge activities, conducted a knowledge management in Latin America. Since the late twentieth century, the Scriptorium Electronic Library, at Universidad Nacional, is its heir and, makes easy its revitalization.